QUALITY PERCEPTION OF ISLAMIC HIGHER EDUCATION INSTITUTION SERVICES: Experience of International Students - Haris, Abd.; Asnawi, Nur (ULUL ALBAB Jurnal Studi Islam, 2020)
This study aims to formulate a special dimension of service quality in Islamic higher education institutions in shaping Islamic culture according to the perceptions of international Muslim students. Using a quantitative approach with exploratory factor analysis, it involved 100 international Muslim students taken from multi-stage proportionated stratified random sampling (probability sampling). The results showed that based on the experience of international Muslim students, the service quality of Islamic higher education institutions included the dimensions of teaching staff competencies, administrative staff competencies, Islamic environment, physical facilities and information technology-based services, all of which can work together in shaping Islamic culture. To support the vision of the internationalization of Islamic higher education institutions, managers must pay attention to these dimensions as a representation of the quality of service felt by international Muslim students to meet their expectations during their studies at Islamic higher education institutions in Indonesia.